2006
DOI: 10.1155/2006/983408
|View full text |Cite
|
Sign up to set email alerts
|

The Catalase –262C/T Promoter Polymorphism and Diabetic Complications in Caucasians with Type 2 Diabetes

Abstract: Catalase is a central antioxidant enzyme constituting the primary defense against oxidative stress. In this study, we investigated whether the functional –262C/T polymorphism in the promoter of catalase gene is associated with the presence of diabetic retinopathy (DR), diabetic nephropathy (DN) and ischemic heart disease (IHD) in 520 Caucasian-Brazilians with type 2 diabetes. The –262C/T polymorphism was also examined in 100 Caucasian blood donors. Patients underwent a clinical and laboratory evaluation consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 19 publications
(36 reference statements)
2
24
0
1
Order By: Relevance
“…Moreover other study from India was reported that GPx1 'C' allele indicated a 1.362 times higher risk of T2DM. Additionally other study from china was reported that there was no statistically significant association between the GPX1-198C/T gene polymorphisms and the risk of DR [18,20,[21][22][23][24][25][26][27][28][29][30]. Serum anti-oxidant activity (GPx) was significantly lower among DR (P=0.001), compared with DNR individuals.…”
Section: N=60 N=70mentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover other study from India was reported that GPx1 'C' allele indicated a 1.362 times higher risk of T2DM. Additionally other study from china was reported that there was no statistically significant association between the GPX1-198C/T gene polymorphisms and the risk of DR [18,20,[21][22][23][24][25][26][27][28][29][30]. Serum anti-oxidant activity (GPx) was significantly lower among DR (P=0.001), compared with DNR individuals.…”
Section: N=60 N=70mentioning
confidence: 99%
“…Free radicals formation in diabetes mellitus and increase over time may play a role in the development of diabetic retinopathy, which is an important complication of the disease [26]. Oxidative stress can influence the expression of multiple genes, including signalling molecules; over expression of these genes may cause mitochondrial dysfunction and peroxidization of the lipid and protein structure, which induce a variety of cellular dysfunctions leading to retinopathy [23]. Elvated oxidized lipids, DNA and protein in diabetics, represent a diminished capacity to decrease toxic reactive oxygen [26].…”
Section: N=60 N=70mentioning
confidence: 99%
See 3 more Smart Citations